Local Positioning With Passive UHF RFID Transponders - Heidrich, Jürgen; Brenk, Daniel; Essel, Jochen; Fischer, Georg; Weigel, Robert; Schwarzer, Stefan (IEEE MTT-S International Microwave Workshop on Wireless Sensing, Local Positioning, and RFID, 2009)
This paper describes the theory of distance measurements with passive UHF transponders using the principle of modulated backscattering. The method was evaluated with the analogue frontend of a passive RFID chip for the UHF range. The chip was designed in a 0.14mum CMOS technology.
elib2cris::1512001600,heidrich2009
Keywords: CMOS technology; chip design; distance measurement; local positioning; modulated backscattering; passive UHF RFID transponder; size 0.14 mum; CMOS integrated circuits; UHF devices; backscatter; distance measurement; microprocessor chips; radiofrequency identification; transponders